Evaluación postcosecha de naranjas (Citrus sinensis L.) almacenadas a temperaturas ambiente y de refrigeración aplicando agentes de recubrimiento. - Molina García, María Alexandra (2014)
The effect of coatings native oranges in postharvest (Citrus sinensis L.) from the site El Arrastradero in Bolívar Canton, during the harvest of June 2013 which were stored at room temperature and refrigerated at 8°C. The coatings were prepared using different hydrocolloid matrix, glycerol as plasticizer and water as solvent, it was applied by dipping method. Completely Randomized Design was used (DCA) and the results were analyze by INFOSTAT Software. The chemical variables were measured at the beginning of the experiment and at the end of each week, while the physical variables were evaluated daily and experimental units were identified at the beginning of the experiment. According to the physiological weight loss (PFP) showed no significant or coatings in storage or temperature difference and their interaction. The best treatments were T2 (coating 1-8°C) for the variables soluble solids (°Brix) and total solids, this treatment was also the less chilling injury reported, for the maturity index and acidity T4 (coating 2-8°C), pH for T8 (uncoated fruits to 8°C). It was determined that the cover 2 has the lowest unit cost of processing provided according to the inputs used of 62 U.S. cents and a total cost of $ 6.00, showing as the best alternative.